(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This paper considers how Ed-Tech companies are using their marketing techniques to improve their online sales and brand presence in the evolving digital education environment. The research uses SWOT analysis to outline the internal strengths and weaknesses as well as the external opportunities and threats in the sector. Among the strengths, one can distinguish individualized learning experience based on artificial intelligence, quality and interactive learning content, an efficient social media marketing, and business collaboration with educational organizations and governmental structures. On the other hand, operational expenses, consumer weary of the aggressive marketing, and internal organizational problems like recent layoffs are all weaknesses. The research outlines significant growth prospects through the high rate of technological development, the ever-growing access to the internet, and governmental efforts to encourage digital education, particularly in the countries with a weak educational infrastructure. Nevertheless, the risks of high competition, the unpredictability of the regulations, and the changes in the market structure require the flexibility and innovativeness in the strategy. The example of Byju shows that the strong suits, such as AI-based personalisation and acquisitions, can make it a leader in the market and also reveal its weaknesses in both scale and perception management. The research design would be both a qualitative and quantitative one that will yield the information by the means of structured surveys and secondary data analysis. Results highlight the paramount necessity to continuously measure the marketing efficacy and modify the strategies to align the customer interaction with the brand integrity. The paper concludes that to maintain competitive edge and facilitate long-term development in the fast-changing education technology market, Ed-Tech companies have to be strategic to leverage their strengths and opportunities and curb the internal and external risks.